Correlation Study of HbA1C and Kidney Failure in Children of Iraq during Dialysis - Nawal M.J. Al- Shammaa (Journal of Global Pharma Technology, 2018)
AbstractDiabetes is the major risk factor for end-stage renal disease (ESRD) worldwide. In advanced chronic kidney disease (CKD), less is known about the predictive value of HbA1c. We enrolled 2401 diabetic patients with stage 3–4 and stage 5 CKD, who were classified into 4 groups according to their baseline HbA1c values (<6%, 6%–7%, 7%–9%, and >9%). During the median follow-up of 3 years, 895 patients developed ESRD, and 530 died. In linear regression analysis, higher HbA1c correlated with higher eGFR in patients with stage 5 CKD but not in stage 3–4 CKD. In Cox regression analysis, a trend toward worse clinical outcomes existed when the HbA1c level exceeded 6% in stage 3–4 CKD, but the significance was only observed for >9%. The hazard ratios (HRs) for ESRD, all-cause mortality and combined CV events with mortality in the group of HbA1c >9% were 1.6 (95% CI, 1.07 to 2.38), 1.52 (95% CI, 0.97 to 2.38) and 1.46 (95% CI, 1.02 to 2.09), respectively. This study demonstrates that the higher HbA1c level is associated higher risks for clinical outcomes in diabetic patients with stage 3–4 CKD but not in stage 5 CKD.Diabetes mellitus (DM) is the leading cause of chronic kidney disease (CKD) worldwide, accounting for approximately 45% of end-stage renal disease (ESRD) cases in the Iraqi children dialysis population. This study was performed on 50 human females aged rang (6-12) years with on diagnosed by examining the patients by Alkademia Teaching Hospital ,also 50 males in addition to 50 healthy were enrolled in the study as control group. Measuring glycated hemoglobin (HbA1c) has been suggested as a means of assessing glycemic control in patients with diabetes, while HbA1c decrease in patients group before and after treated with mixtard. Current guidelines recommend a target HbA1c of approximately 7% for preventing or delaying microvascular complications, including diabetic kidney disease.Patients with DM and in later stages of CKD, whom were mostly excluded from clinical trials. HbA1c levels both appeared to associate with poorer clinical outcomes regardless of the baseline estimated glomerular filtration rate (eGFR). Another study showed that, in dialysis-dependent people with DM, patients with higher HbA1c levels, particularly those without anemia, exhibited poorer survival rates than did patients in the HbA1c range.To elucidate these equivocal results, we analyzed the relationships between HbA1c and the risks of ESRD and mortality in the advanced stages of diabetic CKD and tested whether different CKD stages affected these relationships. Keywords: HbA1c, DM, FBS, Albumin, creatinine, S. urea, CKD.